2023
DOI: 10.1021/acscatal.2c05657
|View full text |Cite
|
Sign up to set email alerts
|

Pretransmetalation Intermediates in Suzuki–Miyaura C–C and Carbonylative Cross-Couplings: Synthesis and Structural Authentication of Aryl- and Aroylnickel(II) Boronates

Abstract: Covalently tethering a supporting ligand to a boron nucleophile allowed typically elusive, kinetically unstable Suzuki–Miyaura (SM) pretransmetalation species to be tamed. This strategy enabled the synthesis and X-ray crystallographic characterization of an organonickel(II) boronate pretransmetalation intermediate. Performing reactions in the presence of carbon monoxide delivered pretransmetalation intermediates in carbonylative SM reactions–aroylmetal boronates. This enabled the X-ray crystal structure of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…1 H NMR spectroscopic analysis of organopalladium(II) boronates 5a – 5f in toluene- d 8 suggested that the respective O–Bpin-uncoordinated structures are readily accessible in solution at ambient temperature (Figures S13, S19, S25, S31, and S37). This is consistent with similar observations with analogous arylpalladium(II) boronates …”
supporting
confidence: 93%
See 4 more Smart Citations
“…1 H NMR spectroscopic analysis of organopalladium(II) boronates 5a – 5f in toluene- d 8 suggested that the respective O–Bpin-uncoordinated structures are readily accessible in solution at ambient temperature (Figures S13, S19, S25, S31, and S37). This is consistent with similar observations with analogous arylpalladium(II) boronates …”
supporting
confidence: 93%
“…The reaction mechanism has been comprehensively investigated, and it is generally acknowledged that transmetalation is the most complicated elementary step of the catalytic cycle . In this regard, typically transient pretransmetalation intermediates in palladium-catalyzed SM couplingsorganopalladium(II) boronatesremain particularly difficult to study due to their inherent kinetic instability (Figure A). …”
mentioning
confidence: 99%
See 3 more Smart Citations